Correlation Between Lecturer Professionalism and Self-Efficacy in College Students - Hidayati, Frieda N. R.; Siswati, Siswati (International Research-Based Education Journal, 2018)
influence, the influence of school environment (including the characteristics of educators), the transitional situation at school, and self-appraisal skills. Lecturers play important roles for the college students in the process of teaching and learning. To increase the quality of the teaching-learning process in colleges, lecturers are required to enhance their professionalism. The research was aimed to assess the correlation between self-efficacy in college students and college student perception on lecturer professionalism. The research was conducted by college students, batch 2016/2017, Faculty of Psychology, Diponegoro University. There were 175 students distributed in four classes. All classes were selected as the research subjects. Data were obtained using two scales namely EDA (Efikasi Diri Akademik/Academic Self-efficacy) Scale and PTPD (Persepsi Terhadap Profesionalisme Dosen/Perception on Lecturer Professionalism) Scale and were then analyzed using simple regression statistics by means of SPSS Software. The result of the research shows the correlation between self-efficacy in college students and college student perception on lecturer professionalism with the value of r = 0.271 with p = 0.000 (p <.01). The research also indicates that lecturer professionalism contributes 7.3% to self-efficacy in college students. It leads to the conclusion that the dominating factor which influences self-efficacy in college students is not lecturer professionalism. Following factors like self-appraisal, peer influence, and family influence might have greater influence, yet further research is needed.Keywords: academic self-efficacy, lecturer professionalism, college students.